Direct Health Care Costs Associated with Asthma in British Columbia. Issue 2 (2010) - Sadatsafavi, Mohsen; Lynd, Larry; Marra, Carlo; Carleton, Bruce; Tan, Wan C; Sullivan, Sean; FitzGerald, J Mark
Abstract : BACKGROUND: A better understanding of health care costs associated with asthma would enable the estimation of the economic burden of this increasingly common disease. OBJECTIVE: To determine the direct medical costs of asthma-related health care in British Columbia (BC). METHODS: Administrative health care data from the BC Linked Health Database and PharmaNet database from 1996 to 2000 were analyzed for BC residents five to 55 years of age, including the billing information for physician visits, drug dispensations and hospital discharge records. A unit cost was assigned to physician/emergency department visits, and government reimbursement fees for prescribed medications were applied. The case mix method was used to calculate hospitalization costs. All costs were reported in inflation-adjusted 2006 Canadian dollars. RESULTS: Asthma resulted in $41, 858, 610 in annual health care-related costs during the study period ($331 per patient-year). The major cost component was medications, which accounted for 63.9% of total costs, followed by physician visits (18.3%) and hospitalization (17.8%). When broader definitions of asthma-related hospitalizations and physician visits were used, total costs increased to $56, 114, 574 annually ($444 per patient-year). There was a statistically significant decrease in the annual per patient cost of hospitalizations (P<0.01) over the study period. Asthma was poorly controlled in 63.5% of patients, with this group being responsible for 94% of asthma-related resource use. CONCLUSION: The economic burden of asthma is significant in BC, with the majority of the cost attributed to poor asthma control. Policy makers should investigate the reason for lack of proper asthma control and adjust their policies accordingly to improve asthma management.